Role of midbrain in the control of breathing in anuran amphibians - Gargaglioni, Luciane H.; Meier, Janice T.; Branco, Luiz G. S.; Milsom, William K. (Amer Physiological Soc, 2007)
The present study was designed to explore systematically the midbrain of unanesthetized, decerebrate anuran amphibians (bullfrogs), using chemical and electrical stimulation and midbrain transections to identify sites capable of exciting and inhibiting breathing. Ventilation was measured as fictive motor output from the mandibular branch of the trigeminal nerve and the laryngeal branch of the vagus nerve. The results of our transection studies suggest that, under resting conditions, the net effect of inputs from sites within the rostral half of the midbrain is to increase fictive breathing frequency, whereas inputs from sites within the caudal half of the midbrain have no net effect on fictive breathing frequency but appear to act on the medullary central rhythm generator to produce episodic breathing. The results of our stimulation experiments indicate that the principal sites in the midbrain that are capable of exciting or inhibiting the fictive frequency of lung ventilation, and potentially clustering breaths into episodes, appear to be those primarily involved in visual and auditory integration, motor functions, and attentional state.
Keywords: control of ventilation; central nervous system; mesencephalon; frog; Rana catesbeiana